2015
DOI: 10.1016/j.ygcen.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of spawning in zebrafish (Danio rerio): Adverse outcome pathways of quinacrine and ethinylestradiol

Abstract: INHIBITION OF SPAWNING IN ZEBRAFISH (Danio rerio): ADVERSE OUTCOME PATHWAYS OF QUINACRINE AND ETHINYLESTRADIOL Madelyne CosmeAdvisor: University of Guelph, 2014Professor. Glen Van Der KraakThis study examined the effects of estrogen receptor agonist, ethinylestradiol, and the phospholipase A 2 inhibitor, quinacrine, on the pathways controlling follicular recruitment, steroidogenesis, oocyte maturation and ovulation and spawning success in the adult zebrafish. Ethinylestradiol and quinacrine both inhibit spawni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 79 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…Our study showed that exposure to PPF causes an imbalance in the proportion of different follicular stages, with an increase in the rate of early stages, that is, follicles with previtelogenic oocytes, and diminished rate and area at later stages, namely follicles with vitellogenic oocytes. Inhibition of oocyte maturation is reported in zebrafish on exposure to following xenoestrogens such as bisphenol A (Yön & Akbulut, 2014), ethinylestradiol (Cosme et al, 2015) and phthalate (Godoi et al, 2021; Santangeli et al, 2017). Cosme et al (2015) reported that ethinylestradiol, an estrogen‐like compound, may act by inhibiting the production of LH, thus preventing the production of maturation‐inducing steroid (DHP) by follicular cells and, thus, inhibiting follicular maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that exposure to PPF causes an imbalance in the proportion of different follicular stages, with an increase in the rate of early stages, that is, follicles with previtelogenic oocytes, and diminished rate and area at later stages, namely follicles with vitellogenic oocytes. Inhibition of oocyte maturation is reported in zebrafish on exposure to following xenoestrogens such as bisphenol A (Yön & Akbulut, 2014), ethinylestradiol (Cosme et al, 2015) and phthalate (Godoi et al, 2021; Santangeli et al, 2017). Cosme et al (2015) reported that ethinylestradiol, an estrogen‐like compound, may act by inhibiting the production of LH, thus preventing the production of maturation‐inducing steroid (DHP) by follicular cells and, thus, inhibiting follicular maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of aromatase expression can disrupt the rate of estrogen production, impacting local and peripheral levels of estrogens within teleosts (Cheshenko et al, 2008), and cyp19a1 is commonly used as a biomarker for estrogenic exposure (Urbatzka et al, 2012). Expression patterns of cyp19a1 are altered after exposure to EE 2 in zebrafish (Urbatzka et al, 2012;Cosme et al, 2015;Liang et al, 2017), roach (Nikoleris et al, 2016), yellow perch (Lynn et al, 2008), rare minnow (Wang et al, 2010) and fathead minnow (Filby et al, 2007;Leet et al, 2015;Feswick et al, 2016). A downregulation of cyp19a1 correlates to depressed synthesis of endogenous estradiol (Villeneuve, 2016), which is a commonly observed endpoint in EE 2 exposure in fish (Gillio Meina et al, 2013;Wang et al, 2019).…”
Section: Impacts Of Ee 2 On Steroidogenic Gene Expressionmentioning
confidence: 99%
“…A downregulation of cyp19a1 correlates to depressed synthesis of endogenous estradiol (Villeneuve, 2016), which is a commonly observed endpoint in EE 2 exposure in fish (Gillio Meina et al, 2013;Wang et al, 2019). This depression of E 2 synthesis may retard follicle growth in developing fish (Cosme et al, 2015). The response of cyp19a1 to EE 2 exposure is variable and impacted by exposure dose and duration, life stage of fish, and species (Johns et al, 2009;Trubiroha et al, 2012;Nikoleris et al, 2016), but the correlation between transcript levels of this gene and circulating plasma E 2 levels are well established in the literature (Perkins et al, 2015;Muth-Köhne et al, 2016).…”
Section: Impacts Of Ee 2 On Steroidogenic Gene Expressionmentioning
confidence: 99%
“…This Special Issue includes four research studies, all of fishes, which consider EDC impacts on reproduction from the wet bench to the field. In their study of Zebrafish, Cosme et al (2015) work within the AOP framework to elucidate the effect of the EDC, ethinylestradiol, and the phospholipase A2 inhibitor, quinacrine on spawning and other apical endpoints of reproductive fitness in adult fish. An article by Kennedy and Smyth (2015) presents the kinetics of plasma levels of estradiol-17b and testosterone after injection of the polycyclic aromatic hydrocarbon, benzo[a]pyrene, a persistent organic pollutant (POP), in mature male Rainbow Trout (Oncorhynchus mykiss).…”
Section: Temperature-sensitive Tri-iodothyronine (T 3 )-Induced Chanmentioning
confidence: 99%